N-phenyl-N?-(2-thienylmethylene)hydrazine - Özçelik, S; Dinçer, M; Sekerci, M; Balaban, A; Özdemir, Ü (Int Union Crystallography, 2004)
The title molecule, C11H10N2S, is almost planar with normal bond lengths and angles. The crystal packing is stabilized by C-H...pi and van der Waals interactions.